The Dewey decimal system - Fowler, Allan (New York Children's Press, 1996)
Explains how the Dewey decimal system of classification for libraries was invented and how it works
Includes bibliographical references (p. 44) and index
Hurg
5
Keywords: Classification -- Dewey decimal